Patient and health service delay in pulmonary tuberculosis patients attending a referral hospital: a cross-sectional study - Harriet Mayanja; Charles Karamagi; Kiwuwa Mpungu S (BMC Public Health, 2005)
Abstract Background Delays in diagnosis and initiation of effective treatment increase morbidity and mortality from tuberculosis as well as the risk of transmission in the community. The aim of this study was to determine the time taken for patients later confirmed as having TB to present with symptoms to the first health provider (patient delay) and the time taken between the first health care visit and initiation of tuberculosis treatment (health service delay). Factors relating to these 'delays' were analyzed. Methods A cross-sectional survey, of 231 newly diagnosed smear-positive tuberculosis patients was conducted in Mulago National referral Hospital Kampala, from January to May 2002. Socio-demographic, lifestyle and health seeking factors were evaluated for their association with patient delay (>2 weeks) and health service delay (>4 weeks), using odds ratios with 95% confidence intervals (CI) including multivariate logistic regression. Results The median total delay to treatment initiation was 12 weeks. Patients often presented to drug shops or pharmacies (39.4%) and private clinics (36.8%) more commonly than government health units (14%) as initial contacts. Several independent predictors of 'patient delay' were identified: being hospitalized (odds ratio [0R] = 0.32; 95% CI: 0.12–0.80), daily alcohol consumption (OR = 3.7; CI: 1.57–9.76), subsistence farming (OR = 4.70; CI: 1.67–13.22), and perception of smoking as a cause of TB (OR = 5.54; CI: 2.26–13.58). Independent predictors of 'health service delay' were: >2 health seeking encounters per month (OR = 2.74; CI: 1.10–6.83), and medical expenditure on TB related symptoms >29 US dollars (OR = 3.88; CI: 1.19–12.62). Perceived TB stigma and education status was not associated with either form of delay. Conclusion Delay in diagnosis of TB is prolonged at the referral centre with a significant proportion of Health service delay. More specific and effective health education of the general public on tuberculosis and seeking of appropriate medical consultation is likely to improve case detection. Certain specific groups require further attention. Alcoholics and subsistence farmers should be targeted to improve accessibility to TB treatment. Continuing medical education about TB management procedures for health providers and improvement in the capacity of TB control services should be undertaken.